Ocular Surface Temperature in Age-Related Macular Degeneration - Andrea Sodi; Sara Matteoli; Giovanni Giacomelli; Lucia Finocchio; Andrea Corvi; Ugo Menchini (Journal of Ophthalmology)
Background. The aim of this study is to investigate the ocular thermographic profiles in age-related macular degeneration (AMD) eyes and age-matched controls to detect possible hemodynamic abnormalities, which could be involved in the pathogenesis of the disease. Methods. 32 eyes with early AMD, 37 eyes with atrophic AMD, 30 eyes affected by untreated neovascular AMD, and 43 eyes with fibrotic AMD were included. The control group consisted of 44 healthy eyes. Exclusion criteria were represented by any other ocular diseases other than AMD, tear film abnormalities, systemic cardiovascular abnormalities, diabetes mellitus, and a body temperature higher than 37.5°C. A total of 186 eyes without pupil dilation were investigated by infrared thermography (FLIR A320). The ocular surface temperature (OST) of three ocular points was calculated by means of an image processing technique from the infrared images. Two-sample t-test and one-way analysis of variance (ANOVA) test were used for statistical analyses. Results. ANOVA analyses showed no significant differences among AMD groups (P value >0.272). OST in AMD patients was significantly lower than in controls (P>0.05). Conclusions. Considering the possible relationship between ocular blood flow and OST, these findings might support the central role of ischemia in the pathogenesis of AMD.